Stereotyping Javanese Workers: An Analysis of Domestic Worker Representation in Movies - Rifan, Muhamad; Ramadhan, Syachrukh; Hardiansyah, Akbar (CV. Era Digital Nusantara, 2024)
Media representations of Javanese domestic servants, especially in the Indonesian film industry, have been characterized by persistent stereotypes. Historically, Javanese laborers have been depicted as loyal, weak, and submissive, reinforcing cultural assumptions about their roles in urban households. This study examines the portrayal of Javanese domestic workers in Indonesian films, emphasizing how these stereotypes reflect broader cultural perspectives on class, ethnicity, and rural-to-urban migration. Using a mixed methods approach, combining qualitative content analysis of five popular Indonesian films with quantitative audience reception surveys and interviews, the research explores both the encoded media messages and how diverse viewers decode them. Findings reveal that films commonly encode Javanese domestic workers as polite, diligent, humble, and submissive, often using cultural markers such as traditional attire and dialects to reinforce these images. However, audience responses vary significantly: about 19% of viewers accept these portrayals uncritically (dominant-hegemonic decoding), 81% engage with them critically, partially accepting but also questioning their relevance and accuracy (negotiated decoding), and 38.1% actively reject the stereotypes, criticizing their role in perpetuating discrimination and calling for more diverse and empowering representations (oppositional decoding). This study highlights the complexity of media reception and underscores the influential role of films in shaping societal perceptions of ethnic minorities, particularly domestic workers. It calls for filmmakers to move beyond reductive stereotypes and to present more nuanced and inclusive narratives that reflect the evolving realities and aspirations of Javanese communities.